Dia de visita: processos educativos emergentes na perspectiva de educadoras de um centro socioeducativo do estado de São Paulo - Brasil - Santos, André Luiz Pereira Alves dos (2021)
This study aimed to analyze the educational processes emerging from the social practice of Visitation Day from the perspective of educators of a Socio-Educational Center in the state of São Paulo. The involvement with the theme arose through my work as an educator in a Center for Socio-Educational Measures of Detention. Driven by the experience in this space and by the contributions of the theme to socioeducation, we established as a research question: what educational processes emerge from the social practice of the Visitation Day, from the perspective of the technical team? We understand that the Visiting Day is one of the pedagogical moments in these institutions and that educational processes emerge that can establish relationships and social bonds that enhance socialization and education. As a starting point, we studied some concepts that permeate the lives and experiences of young people serving detention, the function of the institution as an educational and pedagogical space, and the legal documents regarding Visitation Day. To weave these concepts, we used authors from the research line Social Practices and Educational Processes who discuss concepts of education, dialogicity, humanization, and conscientization such as Paulo Freire, Ernani Maria Fiori, and Enrique Dussel, in dialogue with the socioeducational scholar, Antônio Carlos Gomes da Costa. This is qualitative research and we conducted interviews through videoconferences with three educators from the technical team of a Socio-Educational Center. The material collected in the interviews was transcribed and organized, emerging four focuses of analysis: A) Visiting Day, a unique day: for some, it is eagerly awaited, for others, the worst day of the week; B) The meaning of Visiting Day after meeting with the family; C) So it's the mother who holds the gun; D) The boys were in a great uproar - in times of pandemic COVID-19 communication of young people with their families. The educators emphasize that the Visiting Day generates feelings and sensations in young people and that they are educated in these encounters. In the trajectory of this study, the pandemic of COVID-19 made us rethink the way we do research and the institutions of deprivation and restriction of liberty also had to seek other forms of communication. The meetings held remotely provided moments of learning, reflection, and understanding between the researcher and the educators, contributing to the formation process of both. Therefore, the study makes it possible that the dialog initiated here may contribute to reflections and understandings about the Visiting Day and the field of social-education.